Helicity as isotopy invariant - Azram, Mohammad (Institute of Research and Journals, 2015)
In this paper we will investigate whether or not the writhe of knot is an isotopy invariant? By adding a parallel strand to an oriented knot/link, we will justify that writhe is a useful isotopy invariant. Since helicity has its origin in knot theory, consequently, we will establish that helicity is an isotopy invariant which will be useful to study plasma physics, solar physics and astrophysics.